Research on the Social Mobilization Mechanism for Improving Emergency Response Capability in Unforeseen Events - Wu, Wenya; Fan, Ziyang; Wang, Yan (Transactions on Economics, Business and Management Research, 2024)
This paper investigates the social mobilization mechanism in emergency response through the integration of emergency management and social mobilization theories with various scientific analysis methods. The aim is to explore the importance and development prospects of a reasonable and scientific social mobilization mechanism for enhancing emergency response capabilities in sudden events and to seek practical and valuable improvement measures to enhance the effectiveness of emergency management in emergency response and rescue.